Analisis Perhitungan Dan Pelaporan Pajak Pertambahan Nilai Atas Pengadaan Barang Pada PT. Daya Surya Sejahtera - Windy Ayunda Woroningrum; Nurul Hidayah (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to determine the calculation and reporting of value added tax on the procurement of goods at PT. Daya Surya Sejahtera. Data collection methods used are documentation and interviews. The method is used to obtain data, namely data on purchases and sales in 2019. The stages in analyzing the data in the study are as follows: collecting value added tax data, analyzing the calculation and reporting of value added tax, and drawing conclusions from the results of calculation and reporting of value added tax. Calculation and reporting of Value Added Tax of PT. Daya Surya Sejahtera is in accordance with applicable laws. From the calculation results, PT. Daya Surya Sejahtera is underpaid because the Output Tax is greater than the Input Tax. If there is an underpayment, PT. Daya Surya Sejahtera will make a deposit at the end of the following month.